Contamination of pulse oximeter probes before and after decontamination in two intensive care units - Desai, Farriel (My University, 2020)
Background The internal surfaces of pulse oximeter probes may be overlooked as “hot spots” for pathogenic microorganisms in an intensive care unit (ICU), thereby contributing to the high incidence of hospital acquired infections. Aim The aim of this study was to determine the growth and identification of microorganisms on pulse oximeter probes in the multidisciplinary ICU (MICU) at Charlotte Maxeke Johannesburg Academic Hospital and the burns ICU (BICU) at Chris Hani Baragwanath Academic Hospital before and after decontamination. Methods This was a cross-sectional, descriptive, comparative and contextual study, using purposive sampling. Data was collected from the internal surfaces of 34 pulse oximeter probes in a MICU and BICU. Each pulse oximeter probe was swabbed before and after decontamination. The endemic microorganism profile for the two ICUs was obtained from a laboratory database.Results Internal surfaces of 31 (91%) pulse oximeter probes were contaminated with nine different pathogenic microorganisms pre-decontamination. Acinetobacter baumannii, Klebsiella pneumoniae and Pseudomonas aeruginosa were commonly endemic to both ICUs and were the most frequently isolated microorganisms. Staphylococcus aureus was the most endemic microorganism to both ICUs with only two pulse oximeter probes isolating Staphylococcus aureus on their internal surfaces. Of the internal surfaces of pulse oximeter probes, 6 (18%) remained contaminated post-decontamination, with a microorganism growth reduction of 80% (p=0.0001).Conclusion The internal surfaces of pulse oximeter probes may serve as “hot spots” for an array of pathogens with potential to cause infection and outbreaks in ICUs. Decontamination of the internal surfaces of pulse oximeter probes should be emphasised.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020